Use of Innovative Methods in the Field of Education in the Conditions of the Digital Economy (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The article highlights the relevance of the educational process, its role in society, the advantages of using innovative technologies, the shortcomings of the educational process. At the same time, in the field of education in our country, the advantages of the introduction of digital innovative technologies and a number of effective ways to nurture a young generation capable of comprehensive, talented, enterprising, tireless in pursuing ideas and projects.